CHARACTERISTICS AND OUTCOMES OF ANAPLASTIC LARGE CELL LYMPHOMA PATIENTS- A SINGLE CENTRE EXPERIENCE - Athar, Sohail; Siddiqui, Neelam; Hameed, Abdul (Journal of Ayub Medical College Abbottabad, 2017)
Background: Anaplastic large cell lymphoma (ALCL) is the second most common T cell lymphoma and 2% of all non-hodgkin lymphoma (NHL). It is an aggressive lymphoma with three subtypes, primary cutaneous ALCL, primary systemic ALK +ve ALCL and primary systemic ALK-ve ALCL depending upon rearrangement of Anaplastic Lymphoma Kinase (ALK) gene into ALK +ve and ALK -ve ALCL. Purpose of study is to determine the outcome of patients with ALCL treated at our institute. Methods: In this retrospective analysis, 49 patients with ALCL from 2000 to 2012 were included. Their base line IPI score, stage at presentation, bone marrow involvement, type of chemotherapy, ALK status, extra nodal sites and outcome were recorded. Results: Median age was 34 years (range 20-72 years), with males' predominance, i.e., 75.5 %. At presentation, 7 (14.3%), 12 (24.5%), 14 (28.6%) and 16 (32.7 %) were in stage I-IV, respectively. According to IPI risk categorization, there were 27 (55.1%) in low risk, 12 (24.5%) in low intermediate risk, 8 (16.3%) in high intermediate risk and 2 (04%) in high risk. Seventeen patients (34.7%) were ALK +ve while 21 patients (43%) were ALK +ve and 11 patients (22.4%) had unknown status. Kaplan Meir overall survival (OS) at 5 years was 49.9%. Five-year OS in ALK +ve tumour was 67.4% compared to 39.7% in ALK -ve, p=0.05. Conclusion: Based on our study results, ALCL is common in males with a trend towards better outcome in Alk+ disease. The majority of patients are in advanced stage of disease at the time of presentation. Keywords: Anaplastic large cell lymphoma; Pakistan; Survival; Remission; Chemotherapy